Revitalizing Islamic Education: The Role of Management and Curriculum Design in Addressing Social Change in Pesantren - Luthfi Setya Rahmadani; Setya Raharja (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study aims to examine how Islamic boarding schools (pesantren) manage and redesign their curricula to respond to the challenges of modernization and social change. The present study employs a qualitative research method of a phenomenological nature. This study was conducted at two educational institutions: the Pondok Pesantren Nurul Ummah Kotagede and the Pondok Pesantren Kotagede Hidayatul Mubtadi'ien (PPKHM). The informants in this study consist of the head of the Madrasah Diniyah, the deputy head of the curriculum department of the Madrasah Diniyah, and teachers at the Madrasah Diniyah. The data collection techniques employed in this study encompass in-depth interviews, non-participant observation, and document analysis. The data analysis techniques employed the phenomenological data analysis model of Moustakas through researcher reflexivity, textual description, structural description, and extracting the 'essence' of informants' experiences, which reveal "what" and "how" they experience a phenomenon or concept under study. The research findings indicate that the modernization of management and curriculum design in Islamic education at Islamic boarding schools involves: Firstly, the integration of an educational system that combines the salafiyah (traditional) boarding school typology, which focuses on bandongan, sorogan, memorization, and learning methods based on the Kitab Kuning ‘Classical Islamic Texts’ as the primary reference in learning activities at the boarding school, with the Madrasah Diniyah Takmiliyah educational system, which has classical-based learning and includes levels and stages in the learning process, namely I'dad, Ula or Awwaliyah, Wustho, and Ulya, is of particular interest. Secondly, the institution has initiated a practice-based learning program for final-year students. This program is facilitated through community service, specifically via the PKR (Ramadan Activity Program). Additionally, the institution holds religious study sessions with the objective of developing knowledge and religious education for the community.